Association of eating habits with health perception and diseases among Chinese physicians: a cross-sectional study - Chen, Moxi; Xu, Xuan; Liu, Yinghua; Yao, Ying; Zhang, Pianhong; Liu, Jingfang; Zhang, Qian; Li, Rongrong; Li, Hailong; Liu, Yan; Chen, Wei (Frontiers in Nutrition, 2023)
Background: Some eating habits may be related to the development of gastrointestinal diseases, obesity, and related metabolic dysfunctions. Because of long working hours, and shift schedules, physicians are more likely to form such eating habits and have a high risk of developing these diseases.We aimed to investigate the association between physicians' eating habits and their health perception and diseases.Methods: Between 24 June and 5 August 2020, we performed convenience sampling of in-service physicians in hospitals in mainland China. A questionnaire was administered to collect data pertaining to basic sociodemographic characteristics, eating habits, health-related information such as body mass index classification, and prevalence of common diseases. The associations among eating habits and perceived suboptimal health status, micronutrient deficiency-related diseases, obesity, and related metabolic diseases were analysed.The prevalence of unhealthy eating habits was high: more eating out-of-home (53.4% in hospital canteens, 23.0% in restaurants and takeaways), fewer meals at home, irregular meals (30.5%), and eating too fast (the duration <10 min, 34.6%). Among those with the above eating habits, the prevalence rates of sub-optimal health and disease were higher than among those without the above eating habits.Eating habits such as frequent eating out-of-home, irregular meals, and eating too fast were common among physicians, and were significantly related to perceived sub-optimal health status and disease occurrence.